CHEWING GUM AS A DRUG DELIVERY SYSTEM - M.NAVYA,; N.RAMA RAO, (International Journal of Pharma and Bio Sciences, 2014)
In present era, many research and technological advancements are made in the field of oral drug delivery as it is highly accepted amongst patients.. Chewing gum is one of the very popular oral confectionery products. Medicated chewing gums are prepared by using a water insoluble gum base, elastomers, emulsifiers, fillers, waxes, antioxidants, softeners, sweeteners, food colourings, flavoring agents and drug. This formulation offers both local and systemic effects and has a range of advantages over conventional oral solid dosage forms. It is found effective in the treatment of smoking cessation, pain, obesity, xerostoma, acidity, allergy, nausea, motion sickness, anxiety, dyspepsia, cough. Sustained release of drug can also be achieved by fewer formulary changes during preparation. Medicated chewing gums are an excellent drug delivery system that is convenient, easy to administer anywhere, anytime discretely without water. So, in the near future, one may expect to see major categories of drugs formulated into chewing gum.